The Effect of Digital Learning Applications on Literacy Skills of Junior High School Students - Sarah Rahayu; Maria Kristina Manuputty; Yonas Tangdiesak; Arni Sobon Radha; Ahmad Husin (PT. Anagata Sembagi Education, 2026)
The rapid proliferation of digital technologies has transformed educational landscapes globally, making digital learning applications an increasingly central tool in classroom instruction. This study examined the effect of digital learning applications on the literacy skills of junior high school students, with a specific focus on reading comprehension, digital literacy competencies, and overall learning motivation. Employing a quasi-experimental design with pre- and post-test measurements across intervention and control groups (n = 120 students from two public junior high schools in Central Java, Indonesia), the study implemented three application types: a mobile reading platform, an augmented reality vocabulary tool, and a blended e-module system, over a ten-week period. Results indicated statistically significant improvements in reading comprehension scores (p < .001, d = 0.68), digital literacy indices (p < .001, d = 0.61), and learning motivation (p < .01, d = 0.54) in the intervention group compared to controls. Multivariate regression confirmed that application type, frequency of use, and teacher scaffolding were the strongest predictors of literacy gains. These findings affirm that purposefully designed digital learning applications, when embedded within structured pedagogical frameworks, substantially enhance junior high school students literacy skills and digital competencies. Implications for curriculum designers, classroom teachers, and policymakers are discussed